Scientific production about palliative care and communication in online journals: a scoping review - Cristiani Garrido de Andrade; Isabelle Cristinne Pinto Costa; Maria Eliane Moreira Freire; Thaina Karoline Costa Dias; Jael Rúbia Figueiredo de Sá França; Solange Fátima Geraldo da Costa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to characterize publications about palliative care and communication, with an emphasis on the approaches addressed, disseminated in online journals. Methods: it is a scope review, in which the mnemonic strategy Problem, Concept and Context was used, based on database research. The sample consisted of 86 publications. Results: most publications were written in the English language, published in the journal BMC Palliative Care, and with level of evidence IV. As for the approaches approached, the following stand out: Importance of communication in palliative care; Breaking the bad news in palliative care; Training professionals/staff to communicate in palliative care; and Communication strategies in palliative care. Final Considerations: the review made it possible to map a significant number of publications on palliative care and communication. It is recommended to produce new studies with better scientific evidence that guide the assistance of health professionals.